Aimed information quantity in text. (24th September 2014) - Chen, Jingqiang; Zhuge, Hai; Orgun, Mehmet A.; Orgun, Atilla Elçi; Pieprzyk, Josef; Chefranov, Alexander; Shankaran, Rajan; Wang, Huaxiong; Zhuge, Hai
Summary People often read with aims and reading process significantly influences understanding. This paper defines a new measure of information in text named Aimed Information Quantity in Text by simulating human reading process with reading aims. Aimed Information Quantity in Text reflects not only human memory of words but also relevancy between words emerging in aimed reading process. We demonstrate its application in recommendation. Copyright © 2014 John Wiley & Sons, Ltd.